RETRACTED ARTICLE: Caveolin-1 promotes invasion and metastasis by upregulating Pofut1 expression in mouse hepatocellular carcinoma - Zhang, Cheng (Cell Death Dis, 2019)
Caveolin-1 (Cav-1) is an important structural protein of caveolae and plays an oncogene-like role by influencing protein glycosylation in hepatocellular carcinoma (HCC) cells. However, the mechanism by which Cav-1 promotes invasion and metastasis capacity has not been completely clarified. In this study, we demonstrate that Pofut1 is a fucosyltransferase induced by Cav-1. Mouse Hepa1-6 HCC cells lacking Cav-1 expression exhibited low transcription levels of Pofut1, whereas strong Pofut1 expression was found in high-metastasis-potential Hca-F cells with high levels of Cav-1. Cav-1 activated MAPK signaling and promoted phosphorylation of the transcription factors CREB, Sp1, HNF4A and c-Myc, which bound to the Pofut1 promoter region to induce its transcription. As Notch signaling receptors can be modified with O-fucose by Pofut1, we further showed that Cav-1-induced upregulation of Pofut1 expression activated the Notch pathway and thus enhanced invasion and metastasis by mouse HCC cells in vitro and in vivo. Collectively, our findings reveal a novel mechanism by which Cav-1 promotes tumor metastasis by upregulating expression of Pofut1, suggesting that Cav-1 may function as a new biomarker for HCC.